Quand le monde professionnel rencontre le monde de la recherche et font expérience commune - Richard Wittorski; Philippe Lyet; Gilles Rivet (Recherches en Éducation)
This article aims to approach the collective and collaborative dimensions of research conducting, to understand the effects produced by the engagement of a research activity by and on professionals and to specify the chosen methodological options. For this, it is based on two research on the analysis of professional activities and evolving trades. He is more particularly interested in the conditions and methods of collaboration between researchers and professionals in both research and product effects on committed professionals. He shows that these research devices require time and remain fragile and that it is therefore advisable to "take care". It identifies a tension between professional/institutional challenges and research issues, between professional posture and researcher posture. It highlights professional transformation effects, by building collective dynamics of an interprofessional nature.